EFFECT OF a-TOCOPHEROL AND Β-CAROTENE SUPPLEMENTATION ON MEAT QUALITY AND ANTIOXIDANT CAPACITY OF PIGS FED HIGH-LINSEED OIL DIET - Y. He; K. Wang; L. Wang (Journal of Animal and Plant Sciences, 2010)
The study was to investigate the supplemental effect of α-tocopherol, β-carotene or combination of both on antioxidant capacities in plasma, liver and longissimus dorsi muscle (LM), and meat quality of pigs fed a high-linseed oil diet during the final finishing phase. Forty Duroc×Yorkshire×Landrace growing pigs were allocated to four high-linseed oil (3%) experimental diets formulated as  basal diet (CON), basal diet supplemented with 300 mg/kg α-tocopherol (VE), 100 mg/kg β-carotene (β-C), or combination of α-tocopherol (300 mg/kg diet) and β-carotene (100 mg/kg diet) [VE+β-C]. The meat quality traits, as shown by post-mortem changes of pH value, drip loss and Hunter values, were improved in VE group, but not in β-C or VE+β-C groups. α-Tocopherol concentrations in plasma, liver and meat reflected its dietary treatment and was higher in VE and VE+β-C than CON and β-C. Lipid oxidation products (TBARS) was lower and antioxidation capacity (SOD and T-AOC) was higher in response to VE supplementation, combination of α-tocopherol and β-carotene did not result in superior effects on lipid antioxidant capacity compared with α-tocopherol. Collectively, β-carotene was not qualified for quenching free radicals and combination of β-carotene and α-tocopherol was inferior to single use of α-tocopherol to improve meat quality.
Keywords: α-tocopherol; β-carotene; meat quality; lipid oxidation; linseed oil; finishing pig